PENGABDIAN MASYARAKAT TENTANG DAGUSIBU (DAPATKAN, GUNAKAN, SIMPAN DAN BUANG) OBAT DENGAN BENAR DI SMK IKPI LABUAN PANDEGLANG - Yusransyah Yusransyah; Sofi Nurmay Stiani; Siti Lailatu Zahroh (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Efforts to improve health for the community are very important. This is reinforced by the launching of DAGUSIBU (Get, Use, Store and Dispose of Medicines properly) so that the community is able to understand and be able to implement it in an effort to increase the degree of understanding in terms of medicine, especially how to get, use, store, dispose of drugs properly and create a drug-aware family through the DAGUSIBU program in the SMK IKPI School of Labuan Pandeglang. Material that is socialized is the explanation of the general definition of drugs, drug classification consisting of over-the-counter drugs, limited free drugs, hard drugs, and mandatory drug pharmacies. Then the explanation of the drug preparations and how to use them, special attention is needed so that they are not wrong in using them and the proper and correct storage and disposal procedures for the drugs. It is hoped that through this activity, the ultimate goal to be achieved will be realized, and the community will become a concern in consuming and managing medicines, especially those in the family environment.